EFFECT OF CANVA-ASSISTED DEEP LEARNING MODEL SIZE ON STUDENTS' CRITICAL THINKING SKILLS - Tomi Apra Santosa; Wisnarni; Widiya Yul (Program Studi Pendidikan Bahasa Inggris, 2026)
This study aims to determine the effect of the Canva-assisted deep learning model on students' critical thinking skills in higher education. This study uses a meta-analysis method by calculating the effect size value. This research data comes from 13 national journals indexed by Sinta or Scopus published in 2021-2026. The data search process uses the Springer database, Google Scholar, and ERIC journal. The data analysis technique is quantitative data analysis using the JASP application. The results of this study indicate a positive effect of the Canva-assisted deep learning model on students' critical thinking skills in higher education with an ES value of 0.71 , categorized as moderate effect size. The Canva-assisted deep learning model can encourage student motivation and interest in learning, improving students' critical thinking skills in the 21st century.